2015
DOI: 10.1183/09031936.00191014
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary vascular response patterns during exercise in interstitial lung disease

Abstract: When overt pulmonary hypertension arises in interstitial lung disease (ILD), it contributes to exercise intolerance. We sought to determine the functional significance of abnormal pulmonary arterial pressure (PAP) responses to exercise in ILD.27 ILD patients and 11 age-matched controls underwent invasive cardiopulmonary exercise testing (iCPET). Mean PAP (mPAP) was indexed to cardiac output (Q´T) during exercise, with a mPAP-Q´T slope ⩾3 mmHg·min·L −1 defined as an abnormal pulmonary vascular response. All con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 30 publications
1
35
1
1
Order By: Relevance
“…These results confirm previous reports that a steep mPAP−CO relationship, starting at the upper limit of normal, is associated with a decreased exercise capacity [15,18,[20][21][22][23]. This is presumably related to an afterload limitation of right ventricular flow output, but may require confirmation with exercise measurements of function, cardiac output and oxygen extraction.…”
Section: @Erspublicationssupporting
confidence: 89%
See 1 more Smart Citation
“…These results confirm previous reports that a steep mPAP−CO relationship, starting at the upper limit of normal, is associated with a decreased exercise capacity [15,18,[20][21][22][23]. This is presumably related to an afterload limitation of right ventricular flow output, but may require confirmation with exercise measurements of function, cardiac output and oxygen extraction.…”
Section: @Erspublicationssupporting
confidence: 89%
“…In the second study, DEGANI-COSTA et al [20] report on exercise haemodynamics in 27 patients with interstitial lung disease (ILD) and normal or near-normal mPAP at rest and in 11 matched controls. All control subjects had a mPAP−CO slope <3 mmHg·min·L −1 which confirms, once again, current views on the limits of normal of the pulmonary circulation [9,10].…”
Section: @Erspublicationsmentioning
confidence: 99%
“…Recently, DEGANI-COSTA et al [61] reported on exercise haemodynamics in 27 patients with ILD and normal or near-normal mPAP at rest and 11 matched controls. 15 patients had an abnormally steep mPAP−cardiac output slope ⩾3 mmHg·min·L , indicating an abnormal pulmonary vascular response to exercise.…”
Section: The Response To Exercisementioning
confidence: 99%
“…In the retrospective study of ARMSTRONG et al [71], ILD patients with pulmonary hypertension demonstrated significantly lower end-tidal carbon dioxide tension PETCO 2 and mixed expired carbon dioxide pressure (PECO 2 ) during exercise with a distinctive activity pattern for PECO 2 /PETCO 2 . DEGANI-COSTA et al [72] aimed to determine the functional significance of abnormal pulmonary arterial pressure (PAP) responses to exercise in 27 ILD patients and 11 age-matched controls using invasive cardiopulmonary exercise testing. Mean (m)PAP was indexed to cardiac output (Q′T) during exercise, with a mPAP-Q′T slope ⩾3 mmHg·min·L −1 defined as an abnormal pulmonary vascular response.…”
Section: The Role Of Cardiopulmonary Exercise Test In Ildsmentioning
confidence: 99%